School Discipline and Racial Disparities in Early Adulthood. (April 2022) - Davison, Miles; Penner, Andrew M.; Penner, Emily K.; Pharris-Ciurej, Nikolas; Porter, Sonya R.; Rose, Evan K.; Shem-Tov, Yotam; Yoo, Paul
Despite interest in the contributions of school discipline to the creation of racial inequality, previous research has been unable to identify how students who receive suspensions in school differ from unsuspended classmates on key young adult outcomes. We utilize novel data to document the links between high school discipline and important young adult outcomes related to criminal justice contact, social safety net program participation, postsecondary education, and the labor market. We show that the link between school discipline and young adult outcomes tends to be stronger for Black students than for White students, and that approximately 30% of the Black–White disparities in young adult criminal justice outcomes, SNAP (Supplemental Nutrition Assistance Program) receipt, and college completion can be traced back to inequalities in exposure to school discipline.